THE INFLUENCE OF PERCEIVED RISK ON INTENTION OF USE ONLINE LENDING AMONG THE RESIDENTS OF TANGERANG CITY - Puryatama, Muhammad Farhan; Dewi, Cynthia Sari (Bussman Journal : Indonesian Journal of Business and Management, 2023)
Fintech lending facilitates individuals in need of quick funds for emergencies. However, the community still has reservations due to poorly performing online lending services, such as slow approval processes or fund disbursement. Additionally, there are potential financial losses that may arise from the use of online loans, such as high interest rates or hidden fees. This research aims to analyze how risk factors can influence the Intention to use online loans, such as Performance risk, Financial risk, Social risk, Time risk, Security risk, Legal risk, Psychological risk, and Overall risk. The total sample consisted of 129 individuals in the city of Tangerang. The research method employed a quantitative approach through questionnaires, and the data were processed using Smart PLS version 4.0 for Validity, Reliability, Path Coefficient, R-Square, F-Square, and Q-Square. The results of the study indicate that Performance risk negatifly influences the Intention to use, Financial risk has a negatif impact on the Intention to use, and Security risk affects the Intention to use. However, five risks such as Social risk, Time risk, Legal risk, Psychological risk, and Overall risk do not have a negatif impact on the Intention to use. This research is expected to serve as a reference for the community and online lending service providers in enhancing the Intention to use and reducing risk factors.